If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5a + 11ab + -7a + 15b + -19ab = 0 Reorder the terms: -5a + -7a + 11ab + -19ab + 15b = 0 Combine like terms: -5a + -7a = -12a -12a + 11ab + -19ab + 15b = 0 Combine like terms: 11ab + -19ab = -8ab -12a + -8ab + 15b = 0 Solving -12a + -8ab + 15b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-15b' to each side of the equation. -12a + -8ab + 15b + -15b = 0 + -15b Combine like terms: 15b + -15b = 0 -12a + -8ab + 0 = 0 + -15b -12a + -8ab = 0 + -15b Remove the zero: -12a + -8ab = -15b Combine like terms: -15b + 15b = 0 -12a + -8ab + 15b = 0 The solution to this equation could not be determined.
| m+16=32 | | (24b+14d-10)= | | y/3-4=27 | | 31=7+8x | | p(x)=2x-a^2 | | 8x-9y-3xy-2y+7xy= | | 35-p=12 | | -4(-5t-1+2n)= | | 18-y=15 | | 5x+3x=108 | | 42+a=15 | | 15-n=2 | | 45+1=x | | y-12=22 | | 13(x-9)=15 | | (-20)(4/5) | | 23+p=50 | | 6a^2+30b^2-18b^3a^3= | | 4c+5=6c+1 | | (8x-9x-4)-(4x+3)=4+16 | | -8x+8=16 | | 1/6y=-10 | | x/7=-3/8 | | x+23=67 | | x^2+2x+11=-90 | | Z=9+y | | 9-3(x+7)=4 | | 6d=10+4d | | b^8=96 | | 3x-(-5)=2x-(-6) | | 4a+5=5+2a | | (2+4)*(8-9)= |